Вплив Конвенції про захист прав людини і основоположних свобод на судове рішення у справах про примусове виселення - Стеценко, А. А.; Stetsenko, A. A. (Європейські перспективи. - 2024. - № 3. - С. 84-90, 2024)
Стаття присвячена дослідженню особливостей впливу Конвенції про захист прав людини і основоположних свобод на судове рішення у справах про примусове виселення. Автор наголошує, що дослідження проблеми примусового виселення з точки зору вимог основних актів міжнародного та національного законодавства у сфері примусового виселення є важливим і актуальним як для правової науки, так і для правозастосування. У праці доведено, що при мотивуванні судового рішення про задоволення позову суду слід обов’язково обґрунтовувати дотримання вимог Конвенції про захист прав людини і основоположних свобод. Узагальнюючи проведений аналіз міжнародного та національного законодавства у сфері примусового виселення, слід зазначити, що використання практики ЄСПЛ при розгляді судових справ щодо виселення має на меті значно поліпшити забезпечення прав людини. Стислий огляд основних актів міжнародного та національного законодавства у сфері примусового виселення дозволяє зробити висновки про існування таких особливостей: 1) застосування виселення у випадках, установлених законом; 2) наявність легітимної мети виселення; 3) доведення наявності розумного співвідношення (пропорційності) між метою виселення та засобами, які використовуються для її досягнення (суд визначає та дає оцінку відповідної пропорційності); 4) збереження балансу між публічними та приватними інтересами.

The article is focused on studying specifi c features of the impact of the Convention for the Protection of Human Rights and Fundamental Freedoms on court decisions in cases on forced eviction. The author has emphasized that research of the forced eviction problem from the point of view of requirements of the main acts of international and national legislation in the fi eld of forced eviction is important and relevant both for legal science and for legal enforcement. The author has noted that our state according to the Art. 1 of the Constitution of Ukraine is a social state, whose policy is aimed at creating conditions that ensure a decent life and development of a human being. One of the important conditions is ensuring the right to housing, which is ensured by a number of legal guarantees. The standardized procedure for the eviction or deprivation of housing is one of the important guarantees of the right to housing. The author has indicated that the decision in cases on the eviction is adopted and formalized by the court in compliance with the general rules established in the Civil Procedural Code of Ukraine. A court decision, in accordance with Part 1 of the Art. 263 of the Civil Procedural Code of Ukraine, must be based on the rule of law principles, be legal and justifi ed. The legality of the court decision is determined by the correct application of the norms of substantive law and compliance with the norms of procedural law, taking into account the conclusions on the application of the relevant norms of law set forth in the Supreme Court Rulings. The validity of the decision is defi ned by the completeness and comprehensiveness of the ascertained circumstances, which the parties refer to as the basis of their demands and objections, confi rmed by the evidence examined by the court (the Art. 263 of the Civil Procedural Code of Ukraine). The author of the work has proved that the court must justify the compliance with the requirements of the Convention for the Protection of Human Rights and Fundamental Freedoms when motivating a court decision on allowing a court claim. Having summarized the conducted analysis of international and national legislation in the fi eld of the forced eviction, it should be noted that the application of the ECHR case-law while hearing court cases on the eviction is aimed at signifi cantly improving the insurance of human rights. A brief review of the main acts of international and national legislation in the fi eld of the forced eviction allows us to make conclusions about the existence of the following specifi c features: 1) application of the eviction in cases established by law; 2) the presence of a legitimate purpose of the eviction; 3) proving the existence of a reasonable relationship (proportionality) between the purpose of the eviction and the means used to achieve it (the court determines and assesses the appropriate proportionality); 4) maintaining a balance between public and private interests. A number of conclusions has been made by the results of the research.

Статья посвящена исследованию особенностей влияния Конвенции о защите прав человека и основных свобод на судебное решение по делам о принудительном выселении. Автор отмечает, что исследование проблемы принудительного выселения с точки зрения требований основных актов международного и национального законодательства в сфере принудительного выселения важно и актуально как для правовой науки, так и для правоприменения. В работе доказано, что при мотивировании судебного решения об удовлетворении иска суда следует обязательно обосновывать соблюдение требований Конвенции о защите прав человека и основных свобод. Обобщая проведенный анализ международного и национального законодательства в сфере принудительного выселения, следует отметить, что использование практики ЕСПЧ при рассмотрении судебных дел относительно выселения является целью значительное улучшение обеспечения прав человека. Краткий обзор основных актов международного и национального законодательства в сфере принудительного выселения позволяет сделать выводы о существовании следующих особенностей: 1) применение выселения в случаях, установленных законом; 2) наличие легитимной цели выселения; 3) доказательство наличия разумного соотношения (пропорциональности) между целью выселения и средствами, которые используются для ее достижения (суд определяет и дает оценку соответствующей пропорциональности); 4) сохранение баланса между общественными и частными интересами.
Impact of the Convention for the Protection of Human Rights and Fundamental Freedoms on court decisions in cases on forced eviction
Keywords: цивільне процесуальне право; цивільний процес; цивільне судочинство; Конвенція про захист прав людини і основоположних свобод; судове рішення; судове рішення у справах про примусове виселення; примусове виселення; civil procedural law; civil procedure; civil legal proceedings; Convention for the Protection of Human Rights and Fundamental Freedoms; court decision; court decision in cases on forced eviction; forced eviction; гражданское процессуальное право; гражданский процесс; гражданское судопроизводство; Конвенция о защите прав человека и основных свобод; судебное решение; судебное решение по делам о принудительном выселении; принудительное выселение